Perancangan dan Penerapan Sistem Kendali Marketing pada Industri Air Minum dalam Kemasan Berbasis Customer Relationship Management - Ali Maddinsyah; Untung Nugroho Harwanto; Rifkah Akmalina; Risza Putri Elburdah (Teknik Informatika Universitas Pamulang, 2022)
The demand of drinking water is growing continuously, so that the business prospects are also increasingly promising. This condition becomes a challenge for business doer of drinking water, including CV. Tirta Sasmita. A manual customer data management in CV. Tirta Sasmita causing most of customer data are not well documented, so that it may reduce the number of customers. Customer relationship management (CRM) that consists of human resources, process, and technology is a strategy which can be implemented to improve the customer service to be more effective. This research aims to design a CRM-based application that can be used in marketing control system for business doer of drinking water CV. Tirta Sasmita. This research used qualitative approach method, with descriptive research to arrange a business process flow, and action research to design CRM application using Unified Modelling Language (UML) and interface design. This application was developed using prototype method, in which customer database inside are beneficial to ease the remarketing activity. ‘Add order’ menu in CRM application system is also beneficial in terms of sales trends. There are seven access rights in the application which are based on business process flow of CV. Tirta Sasmita, namely sales counter, field sales, supervisor marketing, manager marketing, finance, surveyor, and legal. This system can be implemented based on process business in CV. Tirta Sasmita.